Application of Au or Ag nanomaterials for colorimetric detection of glucose. Issue 22 (25th October 2021) - Xue, Mingliang; Mao, Wei; Chen, Jisen; Zheng, Fenfen; Chen, Wenhui; Shen, Wei; Tang, Sheng
Abstract : This review mainly introduces several common strategies for the colorimetric determination of glucose by gold or silver nanomaterials. Abstract : In recent years, Au and Ag nanomaterials have been widely used in the determination of glucose owing to their specific properties such as large specific surface area, high extinction coefficient, strong localized surface plasmon resonance effect and enzyme-mimicking activity. Compared with other methods, colorimetric determination of glucose with Au or Ag nanomaterials features the advantages of simple operation, low cost and easy observation. In this review, several typical synthesis methods of Au and Ag nanomaterials are introduced. Strategies for the colorimetric determination of glucose by Au or Ag nanomaterials are elaborated. The challenges and prospects of the application of Au or Ag nanomaterials for colorimetric detection of glucose are also discussed.